Sex chromosome aneuploidy in cytogenetic findings of referral patients from south of Iran - Najmeh Jouyan; Elham Davoudi Dehaghani; Sara Senemar; Ashraf Shojaee; Hossein Mozdarani (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2012)
Background: Chromosome abnormality (CA) including Sex chromosomes abnormality (SCAs) is one of the most important causes of disordered sexual development and infertility. SCAs formed by numerical or structural alteration in X and Y chromosomes, are the most frequently CA encountered at both prenatal diagnosis and at birth. Objective: This study describes cytogenetic findings of cases suspected with CA referred for cytogenetic study. Materials and Methods: Blood samples of 4151 patients referred for cytogenetic analysis were cultured for chromosome preparation. Karyotypes were prepared for all samples and G-Banded chromosomes were analyzed using x100 objective lens. Sex chromosome aneuploidy cases were analyzed and categorized in two groups of Turners and Klinefelter's syndrome (KFS). Results: Out of 230 (5.54%) cases with chromosomally abnormal karyotype, 122 (30%) cases suspected of sexual disorder showed SCA including 46% Turner's syndrome, 46% KFS and the remaining other sex chromosome abnormalities. The frequency of classic and mosaic form of Turner's syndrome was 33% and 67%, this was 55% and 45% for KFS, respectively. Conclusion: This study shows a relatively high sex chromosome abnormality in this region and provides cytogenetic data to assist clinicians and genetic counselors to determine the priority of requesting cytogenetic study. Differences between results from various reports can be due to different genetic background or ethnicity.